Norbornane-based antibacterial agents: Benzyl and benzoyl substituted guanidines - Gareth E. Boer; Shane M. Hickey; Alysha G. Elliott; Frederick M. Pfeffer (Elsevier, 2022)
There is a pressing need to develop new antibiotics to replace those rendered ineffective as a result of widespread antimicrobial resistance. Naturally occurring cationic antimicrobial peptides (CAMPs) exhibit broad-spectrum antibacterial activity and hence are suitable lead compounds for antimicrobial drug discovery programs. The clinical applications of these peptides are limited by poor bioavailability and toxicity and as such we have developed norbornane-based peptidomimetics of these naturally occurring CAMPs. Herein, the synthesis of new antibacterial agents with benzoyl or benzyl substituted guanidines is described along with the evaluation of their antibacterial activity against a range of Gram-positive and Gram-negative pathogens. This study has identified the most active norbornane-based antibacterial compound tested to date (19c), possessing potent activity against methicillin resistant Staphylococcus aureus (MIC ​= ​0.25 ​μg/mL) and Escherichia coli (MIC ​= ​1 ​μg/mL).